"We have to learn about the conditions that set the problem in the course of trying to solve it."
(Noam Chomsky, 2008, On Phases, p.135)

[71] f(x) → b (x → a). ⇔ f_i(x) → b_i (x → a) for all 1 ≦ i ≦ m, provided that f(x) = (f_1(x), . . . f_m(x)) and b = (b_1, . . . b_m).

by | Leave a Comment | Tags:
01 1

https://www.evernote.com/shard/s29/sh/d691b66b-6f42-41a5-8036-7dc14212f8b0/059b33aa8a475513edb54630e0f306da


Previous post[70] √x is continuous in [0, +∞). Next post[72] Basic arithmetic properties of divergent functions

What do you think?

Name required

Website

XHTML: You can use these tags: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>